ChemInform Abstract: Divergent Synthesis of Bioactive Resorcinols Isolated from the Fruiting Bodies of Hericium erinaceum: Total Syntheses of Hericenones A, B, and I, Hericenols B—D, and Erinacerins A and B. Issue 48 (2nd December 2014) - Kobayashi, Shoji; Tamanoi, Hidetsugu; Hasegawa, Yuichi; Segawa, Yusuke; Masuyama, Araki
Abstract Eight bioactive ingredients of the mushroom H.